The effect of academic digital literacy on university students' academic self-efficacy - Kurniawati Muniha Rahman Arpa; Zainul Anwar (Program Studi bimbingan Konseling PPs UNM Makassar, 2026)
The rapid advancement of digital technology in education requires university students to possess adequate academic digital literacy skills to support successful learning. This study aimed to examine the effect of academic digital literacy on university students' academic self-efficacy using a quantitative, simple linear regression analysis. The study involved 306 undergraduate students aged 18-25 years, recruited through convenience (accidental) sampling. Data were collected using the Academic Digital Literacy Scale to measure academic digital literacy and the Academic Self-Efficacy Scale (TASES) to assess academic self-efficacy. Data were analyzed using Jamovi software. The results indicated that academic digital literacy significantly and positively predicted academic self-efficacy (B = 1,35, p < ,001), accounting for 37,6% of the variance in academic self-efficacy. These findings suggest that higher levels of academic digital literacy are associated with stronger academic self-efficacy among university students. Future research is recommended to examine other factors that may contribute to academic self-efficacy, such as learning motivation, social support, and digital learning strategies.